TINGKAT STRES DAN DERAJAT KEPARAHAN ACNE VULGARIS PADA SISWA KELAS III SMAN 1 MAKASSAR - Glenn Javier Dannari Saloko; Melani Rakhmi Mantu (Pusat Riset dan Inovasi Nasional, 2023)
One of the causes of acne vulgaris is stress. According to the WHO (World Health Organization), almost more than 350 million people in the world experience stress, while in Indonesia, the population aged more than 15 years who experience mental emotional disorders or stress reaches 37,728 people based on Riskesdas (Riset Kesehatan Dasar) 2018. Stress can stimulate acne vulgaris by activating the HPA (Hypothalamic Pituitary Adrenal) thereby increasing CRH (Corticotrophin-Releasing Hormone), CRH will increase the production of androgen hormones which trigger the formation of sebum which can clog the sebaceous glands. Acne vulgaris have a psychological impact on teenagers such as dissatisfaction with appearance, lack of confidence, and social dysfunctions like reducing/avoiding social interaction with peers and the opposite sex. Therefore, this study was conducted to find out whether there is a correlation between stress levels and the severity of acne vulgaris at Class III Students of SMAN 1 Makassar in 2021/2022 Period. A cross-sectional, observational analytical methodology is used in this work. The sample size for the study was 102 students. In this study, a dermatologist evaluated the physical severity of acne vulgaris, and Perceived Stress Scale questionnaire was used to evaluate the level of stress. The p-value obtained from the Spearman's rho test employed in this inquiry was 0.317. to come to the conclusion that stress levels and severity of acne vulgaris at Class III Students of SMAN 1 Makassar in 2021/2022 Period are unrelated.